(untitled) (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. Sport contest model is the main indicator of athletes’ sport performance, which allows defining sports trends in general, predicting sports results and also designing directions for training. Research aim was to determine the alteration of goals (as a key indicator) scored by women in Olympic handball in order to carry out trends of modern women handball. Research methods. Data sets were gathered from the International Handball Federation (EHF) website (http:// www.ihf-info.com) covering Olympic Games since Montreal (1976) till London (2012). The data was used from all 248 matches. Statistically significant differences between the independent samples were determined using Student’s t-values of the criterion of a 95% significance level. Research results. In the period of 36 years women’s handball has become more dynamic as teams scored 10.2 goals more in London (25.1 ± 4.5) than in Montreal (14.9 ± 7.4). Teams representing the continent of Europe (23.3 ± 4.2) scored 2.2 goals more on average than teams from other continents (21.1 ± 6.1) during the Olympics. Though the mastery of European teams was better than that of others, the South Korean team, representing the Asian continent, is the first in the rating ranks scale. Discussion and conclusions. Referring to the differences between scored and missed goals by teams which were ess compared Montreal and London Olympic Games we suggest that the mastership of women’s handball is going up and becoming more equal. The phenomenon of South Korean team has allowed to state that the final results in modern women’s handball might be determined not only by the body composition but by other indices of a team or of an individual player’s fitness as well. Keywords: women’s elite sport, key indicators in team handball, national analyses.